Optimalisasi Peran Mahasiswa dalam Program Asistensi Mengajar di SD Inpres 1 Malawei - Lisda Asiyah Putri; Inang Inang; Muh. Fadli Hasa; Dian Saputra; Hayat M. Ohorella (LP3M Universitas Muhammadiyah Sorong, 2023)
One of the teaching campus implementation programs is in the form of teaching assistants that give students the opportunity to support their learning process in primary schools in different villages and towns in Indonesia, especially in the 4T areas (Foremost, Outermost, Disadvantaged and Transmigration areas), one of which is SD Inpres 1 Malawei which is located in Sorong City, West Papua Province. In this program, participating students are responsible for supporting the school with its key processes: the operational aspects. It also helps in teaching and learning processes, technology adaptation and school operations. In addition, the student assistance process is carried out in the form of responsibility in improving literacy and numeracy for students at SD Inpres 1 Malawei, Sorong City. The outcome of this program, especially in the field of education, is that it instills in students empathy and social sensitivity to problems in the lives of those around them, as well as their cross-disciplinary cooperation and problem-solving skills. I have. It enhances the diversity of student knowledge and origins, develops student insight, character and soft skills, and enhances the proper role and contribution of the university and students in the development of society.